Mesenchymal Stem Cells as Therapeutic Candidates for Halting the Progression of Diabetic Nephropathy - Janaina Paulini; Eliza Higuti; Rosana M. C. Bastos; Samirah A. Gomes; Érika B. Rangel (Hindawi Limited, 2016)
Mesenchymal stem cells (MSCs) possess pleiotropic properties that include immunomodulation, inhibition of apoptosis, fibrosis and oxidative stress, secretion of trophic factors, and enhancement of angiogenesis. These properties provide a broad spectrum for their potential in a wide range of injuries and diseases, including diabetic nephropathy (DN). MSCs are characterized by adherence to plastic, expression of the surface molecules CD73, CD90, and CD105 in the absence of CD34, CD45, HLA-DR, and CD14 or CD11b and CD79a or CD19 surface molecules, and multidifferentiation capacity in vitro. MSCs can be derived from many tissue sources, consistent with their broad, possibly ubiquitous distribution. This article reviews the existing literature and knowledge of MSC therapy in DN, as well as the most appropriate rodent models to verify the therapeutic potential of MSCs in DN setting. Some preclinical relevant studies are highlighted and new perspectives of combined therapies for decreasing DN progression are discussed. Hence, improved comprehension and interpretation of experimental data will accelerate the progress towards clinical trials that should assess the feasibility and safety of this therapeutic approach in humans. Therefore, MSC-based therapies may bring substantial benefit for patients suffering from DN.